Chronic exposure to MK-801 leads to olfactory deficits and reduced neurogenesis in the olfactory bulbs of adult male mice - Artem Sinegubov; Vyacheslav Dyachuk (Frontiers in Behavioral Neuroscience, 2024)
BackgroundMK-801 is a drug widely used in preclinical studies to model schizophrenia in animals. Its distinctive feature is the ability to mimic pathological changes in social interactions. Unlike humans, rodents rely heavily on their sense of smell for social interaction. Since, as previously demonstrated, it also impairs neurogenesis, we set out to determine whether olfactory impairment is associated with chronic administration of the drug.MethodsThe mice were divided into two groups, of which one was administered the drug for 3 weeks, and the other only once. Olfaction and social transfer of food preferences were tested after the drug administration period. At the end of the experiment, an immunofluorescence study was performed to determine differences in neurogenesis in the olfactory bulbs.ResultsAn olfactory deficit was observed in animals that received the drug for 3 weeks. These changes were also accompanied by an abnormal lack of food preference in the social transmission test. As a result of a morphological study, a pronounced decrease in the number of new neurons was found in the olfactory bulbs of the animals that had received the drug.ConclusionOur results indicate that at least some of the impairments in social behavior of the animals exposed to NMDA receptor antagonists are likely caused by changes in the sense of smell. These changes are associated with disruptions of neurogenesis.